Application of silver nanoparticles and their relationship with the growth of strawberry - Moreno-Guerrero, Disraeli Eron; López-Collado, Catalino Jorge; Leyva-Mir, Santos Gerardo; Chávez-Franco, Sergio Humberto; Alonso-López , Alejandro; Platas-Rosado, Diego Esteban (Revista Mexicana de Ciencias Agrícolas, 2025)
The use of silver nanoparticles has increased recently due to their application in different areas of science. In plants, they have shown different effects depending on the species and concentration. The present research aimed to evaluate the effect of applying silver nanoparticles via the leaves and roots at increasing doses on the growth of plants of strawberry (Fragaria x ananassa Duch.) cultivar Festival. The experiment was established in a greenhouse in the experimental agricultural field of the UACH, Texcoco, State of Mexico, in 2022 and 2023. Strawberry plants of the Festival cultivar were used as plant material and placed in an open hydroponic system. Subsequently, silver nanoparticles were applied via the leaves (0, 40, 80, 120 and 160 mg L-1) and roots (0, 5, 10, 15 and 20 mg L-1), respectively. At 56 days after the start of treatments, plant height, crown diameter, number of leaves, number of runners, number of flowers and number of fruits were recorded, showing as results that foliar dosing of silver nanoparticles increased crown diameter (25.8%), number of leaves (19.8%), number of flowers (18.3%), number of fruits (28.3%) and number of runners (50%), and root dosing increased plant height (11.9%), number of leaves (14.9%), number of flowers (21.1%), number of fruits (31.8%), and number of runners (31.8%). In conclusion, the application of silver nanoparticles via the leaves and roots increases the growth variables measured in strawberry plants of the Festival cultivar; therefore, silver nanoparticles are an alternative for food sovereignty.